Analysis of Public Opinion on The Hashtag #AniesPresidenRI2024 on Social Media Twitter - Puspitasari, Fingky Ayu; Anggoro, Ayub Dwi (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2024)
In expressing opinions and actively participating in political life, social media is often used and considered one of the important channels. For example, the Hashtag #AniesPresidentRI2024 became a trending topic on Twitter several times after the former Governor of DKI Jakarta, Anies Baswedan, was officially declared by the Chairman of the NasDem Party as a Presidential Candidate in the 2024 Presidential election. The purpose of this study is to determine how the Hashtag #AniesPresidentRI2024 relates to the formation of public opinion on Twitter by using three concepts: public opinion, Twitter social media, and hashtags. This research uses a mixed method that combines both quantitative and qualitative approaches in one study. The results showed that during December 8-13, 2022, there was one dominant actor on Twitter related to the Hashtag #AniesPresidentRI2024, namely @aniesmania. This account led public opinion to provide support and a positive impression of Anies Baswedan. Therefore, it can be concluded that the effect of agenda setting in the formation of public opinion related to a positive image in the Hashtag #AniesPresidentRI2024 has a fairly strong relationship.Keywords: Public opinion, agenda setting, Twitter hashtagsABSTRAKDalam mengekspresikan pendapat dan berpartisipasi aktif dalam kehidupan politik sosial media sering kali digunakan dan dianggap sebagai salah satu saluran penting. Tagar #AniesPresidenRI2024 misalnya, beberapa kali menjadi trending topik di twitter setelah Mantan Gubernur DKI Jakarta Anies Baswedan telah resmi dideklarasikan Ketua umum Partai NasDem sebagai Calon Presiden pada pemilihan Presiden tahun 2024. Tujuan penelitian ini adalah untuk mengetahui Bagaimana Hashtag #AniesPresidenRI2024 memiliki relasi terhadap pembentukan Opini Publik di Media Sosial Twitter untuk dukungan pada Anies Baswedan dengan menggunakan tiga konsep yaitu opini publik, media sosial twitter, dan tagar. Penelitian ini menggunakan metode campuran yang menggabungkan dua metode kuantitatif dan kualitatif dalam satu penelitian. Hasil Penelitian menunjukkan bahwa dalam media sosial twitter pada tanggal 08-13 Desember 2022 terkait dengan Hashtag #AniesPresidenRI2024 memiliki satu aktor dominan yaitu @aniesmania Pada akun tersebut juga lebih menggiring opini publik untuk memberi dukungan dan kesan positif pada anies baswedan sehingga dapat disimpulkan bahwa efek dari agenda setting dalam pembentukan Opini Publik terkait Citra Positif dalam tagar #AniesPresidenRI2024 memiliki relasi yang cukup kuat.Kata Kunci: Opini publik, agenda setting, tagar Twitter